The Effect of Surface Wettability on the Defrost Process - Liu, Yang.; Kulacki, Francis A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This SpringerBrief presents a recent advancement in modeling and measurement of the effect of surface wettability on the defrost process. Carefully controlled laboratory measurements of the defrosting of cooled surfaces are used to reveal the effect of surface wetting properties on the extent and speed of frost removal by melting or slumping. The experiments are accompanied by visualization of frost removal at several defrosting conditions. Analysis breaks the defrost process into three stages according to the behavior of the meltwater. Surface wetting factors are included, and become significant when sufficient meltwater accumulates between the saturated frost layer and the surface. The book is aimed at researchers, practicing engineers and graduate students.
Chapter1: Introduction -- Chapter2: Prior Research -- Chapter3: A Model of the Defrost Process -- Chapter4: Solution Methods -- Chapter5: Experimental Design -- Chapter6: Results -- Chapter7: Conclusion.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Surfaces (Technology).; Thin films; Engineering Thermodynamics, Heat and Mass Transfer; Surfaces, Interfaces and Thin Film; Thermodynamics